member

By forming an ultrathin film with dense hydrophobic groups and a hydrophilically treated metal oxide substrate, the member achieves enhanced alkali resistance and sustained hydrophilicity in alkaline conditions.

JP2025048746APending Publication Date: 2025-04-03TOTO LTD

Patent Information

Application Number
JP2024129967
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-08-06
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Conventional members with ultrathin films containing hydrophilic groups degrade in alkaline environments due to permeation of alkaline components, leading to loss of hydrophilicity and functional properties.

Method used

A substrate with a metal oxide surface is treated with an ultrathin film containing dense hydrophobic groups and a hydrophilic group layer, where the hydrophilic group layer has a thickness and density within a specific range to enhance alkali resistance.

Benefits of technology

The proposed structure maintains excellent alkali durability and hydrophilicity even in long-term exposure to alkaline environments, ensuring the functional properties of the hydrophilic groups are preserved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048746000001_ABST
    Figure 2025048746000001_ABST
Patent Text Reader

Abstract

To provide a member that can continue to exhibit both good alkali durability and hydrophilicity and functionality specific to a hydrophilic group (for example, water scale cleaning properties if anionic) even after prolonged exposure to alkali.SOLUTION: There is provided a member comprising a base material 3 containing a metal oxide, a hydrophobic second functional part 2 formed on the surface of the base material 3 and a hydrophilic first functional part 1 bonded to the second functional part and formed on the surface thereof, wherein the first functional part contains one or more kinds of atoms selected from the group consisting of a sulfur atom (S), a phosphorus atom (P), a nitrogen atom (N) and an oxygen atom (O), as obtained by XPS measurement and exhibits a sputtering time, as obtained by XPS depth direction analysis, is 50 seconds to 1400 seconds, and the second functional part, as obtained by XPS depth direction analysis, has a carbon atom ratio (%) attributable to C-C bonds of 88% or more and exhibits a sputtering time of 105 seconds to 360 seconds.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a member obtained by treating the surface of a substrate containing a metal oxide, and more particularly to such a member capable of retaining the function of hydrophilic groups for a long period of time in an alkaline environment. [Background technology]

[0002] There are widely known techniques for treating the surfaces of various substrates according to the intended use of the component to obtain a component with a desired function on the surface. For example, water is likely to adhere to the surface of a component used in wet areas (wet-related components). When the water adhered to the surface of the wet-related component dries, limescale containing silica and calcium, which are components contained in tap water, is formed on the surface. In addition, dirt such as proteins, sebum, mold, bacteria, viruses, and other microorganisms is likely to adhere to the surface of the wet-related component. In order to prevent limescale and dirt from adhering to the surface of the wet-related component (anti-fouling properties) and to improve the removability of limescale and dirt from the surface (cleanability), there is known a technique for coating and modifying the surface of the substrate of the wet-related component with a layer or film having desired properties.

[0003] As an example of such a technique, JP 2016-020461 A (Patent Document 1) describes a method in which the surface of pottery is treated with a silane coupling agent (specifically, 3-acryloxypropyltrimethoxysilane) containing a radical reactive functional group to form a hydrophobic primer layer, and a coating composition containing a hydrophilic compound containing a radical reactive functional group and an alkali metal salt of a sulfonic acid group is applied to the primer layer to form a hydrophilic coating film on the pottery surface via the hydrophobic primer layer. According to Patent Document 1, the obtained hydrophilic coating film is said to have good durability (paragraph 0083) and washability (stain removability, paragraphs 0084-0085).

[0004] Polymer Research Journal, Vol. 70, No. 8, pp. 419-431 (Aug., 2013) (Non-Patent Document 1) describes the formation of a hydrophobic monolayer by treating the surface of a substrate (silicon substrate, silica particles, thin gold film) with a silane coupling agent (specifically, 11-(2-bromo-2-methyl)propionyloxy)undecyltrichlorosilane) for the purpose of application to medical or biocompatible materials, and the creation of a betaine polymer brush layer (biomedical surface) on this hydrophobic monolayer.

[0005] Polymer, Vol. 69, No. 8, pp. 402-431 (Aug., 2020) (Non-Patent Document 2) describes the adhesion of substrates using electrostatic attractive interactions between polyanion and polycation electrolyte polymer brushes, and the hydrophilicity and size exclusion effect of zwitterionic polymer brushes to suppress biological fouling such as barnacle larvae. While it is expected to be a useful tool for surface functionalization, the main reason for the scarcity of industrial applications is that it is difficult to prevent the deterioration of polymer brushes due to oxidative decomposition caused by light and heat and hydrolysis in water.

[0006] Japanese Patent Publication No. 2022-088296 (Patent Document 2) describes a biosensor having a chain structure molecule in which a hydrophobic region, a functional region, and a probe molecule are linked in this order on the surface of a substrate. In the [Example] of Patent Document 2, a hydrophobic monolayer made of (2-bromo-2-methyl)propionyloxypropyltrimethoxysilane is formed on the surface of a silicon substrate, or a hydrophobic monolayer made of α-bromobutyrate-11-undecanethiol is formed on the surface of a gold substrate as a hydrophobic monolayer containing a binding functional group, a poly(tert-butyl methacrylate) (PtBMA) layer is formed on this hydrophobic monolayer, and then the PtBMA layer is treated with hydrochloric acid to form a two-layer structure of a hydrophobic polymer brush layer (PtBMA) and a hydrophilic polymer brush layer (PtBMA-COOH) on the substrate via the hydrophobic monolayer. According to Patent Document 2, the hydrophobic polymer brush layer prevents the migration of low molecular weight substances to the substrate, and the hydrophilic polymer brush layer prevents non-specific adsorption of biopolymers (paragraphs 0013 and 0016). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2016-020461 A [Patent Document 2] Patent Publication No. 2022-088296 [Non-patent literature]

[0008] [Non-Patent Document 1] Polymer Papers, Vol. 70, No. 8, pp. 419-431 (Aug., 2013) [Non-Patent Document 2] Polymer, Vol. 69, No. 8, pp. 402-431 (Aug., 2020) Summary of the Invention [Problem to be solved by the invention]

[0009] Some wet-area components are exposed to an alkaline environment for a long time due to the use of alkaline detergents, etc. The present inventors have discovered that a conventional or existing component, which has an ultra-thin film containing hydrophilic groups (the ultra-thin film containing hydrophobic groups and the ultra-thin film containing hydrophilic groups are collectively referred to as "functional ultra-thin films") provided on the surface of a base material (hereinafter, sometimes simply referred to as "base material") containing a metal oxide, via an ultra-thin film containing hydrophobic groups, and in which the number of carbon atoms of the hydrophobic groups constituting the ultra-thin film containing hydrophobic groups is small, or the proportion of molecules containing hydrophobic groups in the ultra-thin film containing hydrophobic groups is low, i.e., the density of the ultra-thin film containing hydrophobic groups is low, is attracted to the ultra-thin film containing hydrophilic groups due to its affinity with the ultra-thin film containing hydrophilic groups, when used in an alkaline environment. The present inventors have found a new problem in which the alkaline components easily permeate the hydrophobic ultra-thin film and induce hydrolysis of the components that constitute the bond between the hydrophobic ultra-thin film and the substrate and the components that constitute the surface of the substrate, resulting in the destruction of the bond at the interface between the substrate and the hydrophobic ultra-thin film in preference to the molecules that constitute the hydrophilic ultra-thin film, the molecules that constitute the hydrophobic ultra-thin film, and the linkers at the interface between the hydrophilic ultra-thin film and the hydrophobic ultra-thin film. Furthermore, the hydrophobic ultra-thin film peels off from the substrate, causing the entire functional ultra-thin film to disappear, i.e., the wet-area component loses its function.

[0010] The present inventors have found and confirmed that the degree of permeability of an alkaline component to an ultra-thin film containing hydrophobic groups is closely related to the film thickness and / or density of the film. Furthermore, they have found and confirmed a new problem that when the amount of the ultra-thin film containing hydrophilic groups is below a certain range, the hydrophilicity is lost even if the ultra-thin film containing hydrophobic groups remains. In other words, they have found and confirmed that in order to improve the alkali resistance of a functional ultra-thin film, it is necessary that the film thickness of the ultra-thin film containing hydrophilic groups is above a certain range and that the film thickness and / or density of the ultra-thin film containing hydrophobic groups is above a certain range. Furthermore, it was found that the film thickness of the ultra-thin film containing hydrophilic groups and the film thickness and / or density of the ultra-thin film containing hydrophobic groups are closely related to the sputtering time of the ultra-thin film containing hydrophilic groups and the ultra-thin film containing hydrophobic groups, which is obtained by depth profiling of the finished member using a combination of X-ray photoelectron spectroscopy (XPS) measurement and sputtering using Ar ions, and the optimum ranges for the film thickness of the ultra-thin film containing hydrophilic groups and the hydrophobicity of the ultra-thin film containing hydrophobic groups for solving the above-mentioned problems were successfully quantified using the above-mentioned sputtering time as an index. In this way, a member comprising a functional ultra-thin film consisting of an ultra-thin film containing hydrophobic groups and an ultra-thin film containing hydrophilic groups provided on the surface of a substrate containing a metal oxide, which can withstand long periods of exposure to an alkaline environment, The present invention is based on these findings. [Means for solving the problem]

[0011] The component according to the invention comprises: A substrate comprising a metal oxide; A second functional portion formed on the surface of the base material; a first functional part which is bonded to the second functional part and contains one or more atoms selected from the group consisting of a sulfur atom (S), a phosphorus atom (P), a nitrogen atom (N) and an oxygen atom (O); A member comprising: the outermost surface of the member is the outermost surface of the first functional portion, When the surface of the member is analyzed in the depth direction by X-ray photoelectron spectroscopy (XPS) in combination with argon sputtering, the member satisfies the following requirements (I), (II), and (III): (I) the sputtering time T1 (t1-0) from when argon sputtering is started from the surface of the member in accordance with the following condition 1 (0 seconds) to when the first functional portion is deemed to have disappeared by satisfying the following requirement A (t1 seconds) is 50 seconds or more and 1400 seconds or less; (II) at the time when the first functional portion is deemed to have disappeared because it satisfies the following requirement A, an XPS scan analysis is performed in accordance with the following condition 2, and peak separation is performed in the range from 279.0 eV to 292.0 eV in the C1s measurement range, and the ratio of the peak area intensity of the carbon atom attributable to a C-C bond (284.8 eV) to the sum of the peak area intensity of the carbon atom attributable to a C-C bond (284.8 eV), the peak area intensity of the carbon atom attributable to a C-O bond (287.1 eV), and the peak area intensity of the carbon atom attributable to an O=C-O bond (289.2 eV) is 88% or more and 100% or less; (III) the second functional part is argon-sputtered from its surface in accordance with the following condition 1, and the sputtering time T2 (t2-t1) until the second functional part is deemed to have disappeared by satisfying the following requirement B (t2 seconds) is 105 seconds or more and 360 seconds or less; Fulfilling The condition 1 is X-ray conditions: Monochromatic AlKα radiation, 30W, 12kV Analysis area: 200μmφ Neutralization gun conditions: 0.1V, 200μA Photoelectron take-off angle: 90° Time Per Step: 10 ms Sweep: 2 times Pass energy: 200eV Survey energy range (step size): 0eV-1350eV (0.1eV) Inert gas species: Ar Sputtering voltage: 200V Sputtering area: 2mm x 2mm Sputter cycle: 5 seconds and The above requirement A is: After charge correction with the C1s peak set at 284.8 eV, the background is removed by the Shirley method for the peaks based on the identified elements, the peak area intensity is calculated, and then an analysis process is performed in which the peak area intensity is divided by the sensitivity coefficient specific to the device that is preset in the data analysis software. The atomic concentrations of sulfur atoms, nitrogen atoms, and phosphorus atoms, with the total number of detected atoms as the modulus, are each 1.0 atm% or less, and the oxygen atomic concentration excluding the oxygen atomic concentration derived from oxides contained in the base material is 6.0 atm% or less. and The condition 2 is X-ray conditions: Monochromatic AlKα radiation, 30W, 12kV Analysis area: 200μmφ Neutralization gun conditions: 0.1V, 200μA Photoelectron take-off angle: 90° Time Per Step: 50 ms Sweep: 5 times Pass energy: 55 eV Analyzed element (energy range, step size): C1s (279.0 eV-292.0 eV, 0.05 eV) Inert gas species: Ar and The above requirement B is: After charge correction with the C1s peak set at 284.8 eV, the background is removed by the Shirley method for the peaks based on the identified elements, the peak area intensity is calculated, and then the data is divided by the device-specific sensitivity coefficient preset in the data analysis software. The carbon atom concentration, with the total atoms detected as the modulus, is 2.5 atm% or less. It is characterized by: Effect of the Invention

[0012] According to the present invention, there is provided a member which can continue to exhibit excellent alkaline durability even when exposed to an alkaline environment for a long period of time, and which can therefore continue to exhibit, without impairing, the inherent properties (e.g., hydrophilicity or water stain cleaning properties) of an ultra-thin film containing hydrophilic groups or functional groups formed on a dense ultra-thin film containing hydrophobic groups. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram showing an example of the configuration of a member according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of the configuration of a member according to the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of a state in which a second functional part, which is a mixed dense film, is formed on a substrate (a state before a first functional part is formed on the second functional part). [Figure 4] 4 is a diagram illustrating a sputtering time of a first functional unit and a sputtering time of a second functional unit. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Materials An example of the configuration of a member according to the present invention will be described with reference to Fig. 1. A member 10 according to the present invention comprises a base material 3, a second functional part 2 formed on the surface of the base material 3, and a first functional part 1 bonded to the second functional part 2. The outermost surface of the member 10 is the outermost surface of the first functional part 1. In other words, the first functional part 1 is formed on the surface of the second functional part 2.

[0015] The component according to the present invention is preferably used in an environment where it is exposed to water and / or pollutants, and more preferably used around water. In the present invention, examples of "wet areas" include bathrooms, toilets, washrooms, and kitchens. Examples of members according to the present invention include bathroom floors, bathtubs, walls, ceilings, counters, aprons, drains, mirrors, etc.; toilet bowls, tanks, toilet lids, toilet seats, heated toilet seats, heated toilet seats, etc.; washbasins, washbasin counters, mirrors, lighting, faucets, drains, cabinets, washing machine pans, etc.; kitchen sinks, counters, faucets, drains, dishwashers, dish dryers, cooking ranges, kitchen hoods, extractor fans, etc.

[0016] Base material In the present invention, the substrate 3 comprises a metal oxide. In one embodiment of the present invention, the metal oxide is preferably contained on the surface side of the substrate 3, and more preferably contained in a region in contact with the surface of the substrate 3, i.e., a region including the surface of the substrate 3. Even more preferably, the region in contact with the surface of the substrate 3 is a layer made of a metal oxide.

[0017] In another embodiment of the present invention, as shown in Fig. 2, the substrate 3 preferably comprises a base material 3-2 and a region 3-1 containing a metal oxide on the surface side of the substrate 3. It is more preferable that the region 3-1 is a region in contact with the surface of the substrate 3. Even more preferably, the region in contact with the surface of the substrate 3 is a layer made of a metal oxide. In the present invention, the material of the base material 3-2 may be, for example, ceramic, glaze, sanitary ware, glass (e.g., quartz glass, soda lime glass, etc.), metal (e.g., SUS, brass, nichrome, etc.), etc., and the structure of the base material 3-2 may be, for example, a laminate, an alloy, or a plating.

[0018] In another embodiment of the present invention, the substrate preferably comprises a metal oxide.

[0019] <Metal oxide> The metal oxide contained in the substrate 3 may be, for example, an oxide or composite oxide of one or more metal elements selected from the group consisting of Cr, Ni, Si, Al, Zr, Ti, Sn, Zn and Fe, or a mixture thereof.

[0020] Second Functional Section In the present invention, the second functional part 2 is configured in a region sandwiched between the substrate 3 and the first functional part 1. The second functional part preferably contains hydrophobic groups, and the hydrophobic groups form a dense layer. The hydrophobic groups preferably contain hydrocarbon groups. The hydrocarbon groups are preferably linear. The second functional part may contain a plurality of types of hydrocarbon groups with different chain lengths. The second functional part preferably has linear hydrocarbon groups oriented perpendicularly to the substrate surface to form a dense hydrocarbon layer. In other words, it is preferable that one end of the hydrocarbon group is on the substrate side and the other end is on the first functional part side. In other words, the second functional part is preferably a dense ultrathin film, advantageously a monolayer, formed by the self-organization of a large number of molecules containing linear hydrocarbon groups.

[0021] In the second functional part, the hydrocarbon group is preferably a linear hydrocarbon group having 12 to 30 carbon atoms, and more preferably a linear hydrocarbon group having 23 to 29 carbon atoms. The film thickness of the second functional part depends on the chain length of the linear hydrocarbon group. In the present invention, the second functional part is an ultra-thin film, and the length of the linear hydrocarbon group is preferably about 1.1 to 3.8 nm. In the present invention, an ultra-thin film means a thin film having a film thickness of more than 0 nm and not more than 100 nm.

[0022] The second functional part in the present invention is a high-density linear hydrocarbon group-containing ultrathin film, preferably a monolayer, and thus exhibits excellent hydrophobicity. The density and thickness of the second functional part are closely related to the sputtering time of the second functional part, which is obtained by performing depth profile analysis of the member by X-ray photoelectron spectroscopy (XPS) in combination with sputtering using Ar ions, and can be quantitatively determined using this sputtering time as an index.

[0023] In the hydrophobic primer layer described in Patent Document 1, the structure contributing to hydrophobicity is the propyl group of the silane coupling agent (3-acryloxypropyltrimethoxysilane), which has 3 carbon atoms. In the ultra-thin film containing a hydrophobic group described in Non-Patent Document 1, the structure contributing to hydrophobicity is the undecyl group of the silane coupling agent (11-(2-bromo-2-methyl)propionyloxy)undecyltrichlorosilane), which has 11 carbon atoms. In the ultra-thin film containing a hydrophobic group described in Patent Document 2, the structure contributing to hydrophobicity is the propyl group (carbon number 3) of ((2-bromo-2-methyl)propionyloxypropyltrimethoxysilane) and the undecyl group (carbon number 11) of (α-bromobutyrate-11-undecanethiol). In other words, the hydrophobicity of the ultra-thin film containing a hydrophobic group disclosed in these documents is inferior to the hydrophobicity of the second functional part in the present invention.

[0024] It is preferable that the hydrocarbon group contained in the molecule constituting the second functional part is chemically bonded to the first functional part via a linker. It is more preferable that the end of the hydrocarbon group contained in the molecule constituting the second functional part on the first functional part side reacts with the reactive functional group chemically bonded to the end of the first functional part, and thus the hydrocarbon group is chemically bonded to the first functional part via the linker.

[0025] The second functional part is preferably chemically bonded to the substrate surface, and more preferably, a hydrocarbon group contained in the molecule constituting the second functional part is chemically bonded to the substrate surface. It is even more preferable that the hydrocarbon group contained in the molecule constituting the second functional part is chemically bonded to the substrate via a functional group capable of bonding to a metal oxide contained in the substrate surface, that is, by the functional group being chemically bonded to a metal atom of the metal oxide contained in the substrate surface.

[0026] The functional group contained in the molecule constituting the second functional part, which is bonded to the end of the hydrocarbon group on the substrate side and can bond to the metal oxide contained in the substrate surface, is preferably a hydrolyzable silyl group. The hydroxyl group or hydrolyzable group contained in the hydrolyzable silyl group preferably functions as a bonding point with the substrate. In other words, the hydroxyl group contained in the hydrolyzable silyl group, or the hydroxyl group obtained by hydrolysis of the hydrolyzable group, or the hydrogen atom contained in the hydroxyl group undergoes dehydration condensation with the functional group (such as a hydrogen atom or a hydroxyl group) present on the surface of the substrate.

[0027] <Linker> The linker is chemically bonded to the first functional part and the second functional part. The linker is preferably composed of an ester bond (-COO-), a urea bond (-NH-CO-NH-), a urethane bond (-NH-COO-), an amide bond (-NH-CO-), or an ether bond (-O-) on the second functional part, and serves to bond the first functional part and the second functional part.

[0028] It is not necessary that all of the molecules constituting the second functional part have a linker, and the molecule may be a mixture of molecules having a linker and molecules having no linker.

[0029] Generally, a linker is bulky compared to a hydrocarbon group, and a dense second functional part is difficult to form due to steric hindrance. For example, the (2-bromo-2-methyl)propionyloxy group of the silane coupling agent (11-(2-bromo-2-methyl)propionyloxy)undecyltrichlorosilane) described in Non-Patent Document 1 is bulky compared to an undecyl group and causes steric hindrance. In addition, the α-bromobutyrate group of (α-bromobutyrate-11-undecanethiol) described in Patent Document 2 is also bulky compared to an undecyl group and causes steric hindrance. In addition, in Patent Document 2, tert-butyl methacrylate is bonded to α-bromobutyrate-11-undecanethiol, which causes steric hindrance, so that the hydrophobic polymer brush layer (PtBMA) formed on such an ultra-thin film containing a low-density hydrophobic group is forced to follow the low density of the ultra-thin film containing a hydrophobic group, and is considered to be a layer of similar low density. In addition, in the hydrophobic polymer brush layer (PtBMA), the structure that contributes to the hydrophobicity is the repeating structure of tert-butyl groups, and the density of the hydrophobic structure in the hydrophobic polymer brush layer is thought to be lower due to steric hindrance caused by the tert-butyl groups. In addition, the hydrophobic polymer brush layer is insufficient in preventing the permeation of water molecules because the oxygen atoms derived from the ester bonds in the side chains have polarity.

[0030] The molecules constituting the second functional part are preferably a mixture of a linear alkylsilane having a binding functional group 23 at the end of the first functional part side described later and a linear alkylsilane not having a binding functional group 23, as shown in FIG. 3, and the carbon numbers of these two types of alkylsilane are approximately the same, preferably the difference in the carbon numbers is 0 to 5, and more preferably the carbon number of the linear alkylsilane having the binding functional group is large. By adopting such a structure, the intermolecular force between the alkyl groups 22 of the second functional part is increased, and the second functional part is well densified. In this specification, a film densified by the above mixture is defined as a "mixed dense film". Since the second functional part is hydrophobic and dense, an alkaline component is less likely to permeate the second functional part in an alkaline environment, and hydrolysis of the bond between the ultra-thin film containing a hydrophobic group and the substrate is suppressed, so that the member can obtain excellent alkali resistance. In the present invention, the carbon number of the linear alkylsilane having the binding functional group is preferably 12 to 30, more preferably 23 to 29.

[0031] First Functional Section The first functional part in the present invention is bonded to the above-mentioned second functional part and contains one or more atoms selected from the group consisting of a sulfur atom (S), a phosphorus atom (P), a nitrogen atom (N) and an oxygen atom (O). These atoms constitute a hydrophilic group. Therefore, the first functional part has hydrophilicity. In the first functional part of the present invention, the atomic concentration of each of sulfur atoms (S), phosphorus atoms (P), nitrogen atoms (N) and oxygen atoms (O) is preferably 1.0 to 50.0 atm %, and more preferably 2.0 to 39.0 atm %.

[0032] Quality of the first functional part The first functional part in the present invention preferably forms a polymer layer containing a CC bond and having a hydrophilic group, more preferably forms a polymer layer containing a CC bond and having an ionic hydrophilic group, and further preferably forms a polymer brush layer containing a CC bond and having an ionic hydrophilic group.

[0033] Furthermore, as a surface characteristic of the first functional part, it is preferable that the static contact angle of water as defined in JIS R 3257 (2018) is 70° or less, more preferably 50° or less, and even more preferably 30° or less.

[0034] <Hydrophilic group> The hydrophilic groups in the first functional part are classified into ionic and nonionic, and the ionic hydrophilic groups are further classified into cationic, anionic, and zwitterionic hydrophilic groups. An example of a cationic hydrophilic group is quaternary ammonium (N + ), sulfonium (S + ), phosphonium (P + Examples of anionic hydrophilic groups include carboxylic acid or its salt (-COO - ), phosphonic acid or its salt (-PO42 - , -HPO4 - ), sulfonic acid or its salt (-SO3 - In the present invention, the amphoteric hydrophilic group means a hydrophilic group having at least one cationic hydrophilic group and one anionic hydrophilic group in the same molecule, and among them, a quaternary ammonium salt is included as a cation and -SO3 - Sulfobetaines containing quaternary ammonium as the cation and -PO4 as the anion in the molecule. 2- Phosphobetaines containing quaternary ammonium as a cation and -SO3 as an anion are preferred. - Examples of nonionic hydrophilic groups include a hydroxyl group (-OH), an ether bond (-O-), an ester bond (-COO -), urea bond (-NH-CO-NH-), urethane bond (-NH-COO-), and amide bond (-NH-CO-). Functions exhibited by the first functional part containing these hydrophilic groups include antibacterial properties if the hydrophilic group is cationic, limescale cleaning properties if the hydrophilic group is anionic, protein non-adsorption properties if the hydrophilic group is zwitterionic, and ion non-adsorption properties if the hydrophilic group is nonionic. Examples of proteins generated in water-related components include human keratin. In addition, in the present invention, in order to cause the first functional part to exhibit multiple functions, compounds having cationic, anionic, zwitterionic, and nonionic hydrophilic groups can be mixed in any ratio with the first functional part. For example, by mixing a compound having an anionic hydrophilic group with a compound having a zwitterionic hydrophilic group, it is possible to simultaneously exhibit the anionic-derived limescale cleaning properties and the zwitterionic-derived protein non-adsorption properties; by mixing a compound having a zwitterionic hydrophilic group with a compound having a nonionic hydrophilic group, it is possible to simultaneously exhibit the zwitterionic-derived protein non-adsorption properties and the nonionic-derived ion non-adsorption properties; and by mixing a compound having a cationic hydrophilic group with a compound having a zwitterionic hydrophilic group, it is possible to simultaneously exhibit the cationic-derived antibacterial properties and the zwitterionic-derived protein non-adsorption properties.

[0035] By making the second functional part hydrophobic and dense, it is possible to greatly reduce the hydrolysis rate of the bond group with the substrate, but when exposed to an alkaline environment for a long period of time, the bond group gradually hydrolyzes, and the constituent molecules of the second functional part and the constituent molecules of the first functional part that are bonded to the said molecules via a linker are both detached. As a result, the hydrophilic groups constituting the first functional part do not sufficiently cover the surface of the member, and the substrate or the second functional part is exposed locally, which becomes the starting point for adsorption of contaminants and inhibits the functions of the first functional part (hydrophilicity, antifouling, etc.). When the first functional part has a film thickness of a certain level or more, when a part of the first functional part and the second functional part are detached, the molecules constituting the first functional part that are present in close proximity to the detached part cover the surface after detachment, preventing the exposure of the substrate or the second functional part to the outermost surface, and the functions of the hydrophilic groups constituting the first functional part can be maintained for a long period of time.

[0036] Identifying the material In the present invention, the identification of a member using XPS measurement is preferably divided into cleaning of the member, identification of the first functional part, and identification of the second functional part, which will be described later, and these measurements are preferably performed consecutively. In other words, it is preferable not to remove the member from the apparatus between each measurement, and not to provide a waiting time between each measurement. By performing the measurements consecutively as described above, it is possible to prevent the sample surface from being affected by contamination resulting from the environment or operation.

[0037] <Cleaning of components> It is preferable to clean the surface of the component before XPS measurement. For cleaning, it is preferable to use a neutral detergent (product name: Clean Ace, manufactured by AS ONE) and a urethane sponge. It is preferable to use a urethane sponge layer of "Scotch-Brite" ("Bath Shine" antibacterial sponge, no abrasive particles, manufactured by 3M Japan, BM-22K; "Scotch-Brite" and "Bath Shine" are registered trademarks of 3M Company) cut into a cube of 2 cm on each side. After soaking the urethane sponge in water and adding a neutral detergent to create a lather, it is preferable to press the sponge against the surface of the first functional part with a load of about 100 g / cm2 and wash it by moving it back and forth five times. It is preferable to then rinse thoroughly with ultrapure water.

[0038] <Identification of the first functional part> The first functional part can be identified by static contact angle measurement of water, XPS measurement, and depth profile analysis using a combination of XPS measurement and sputtering using Ar ions, as specified in JIS R 3257 (2018). This depth profile analysis using a combination of XPS measurement and sputtering using Ar ions is referred to as "XPS depth profile analysis." K-ALPHA (manufactured by Thermo Scientific) can be used as the XPS device. A spectrum can be obtained by performing XPS depth profile analysis under the following XPS measurement conditions.

[0039] <Water contact angle> The contact angle of water on the surface of the first functional part can be measured using a contact angle meter (for example, model number: DMs-401, manufactured by Kyowa Interface Science Co., Ltd.). Immediately before the measurement, it is preferable to clean the surface of the first functional part, that is, the surface of the member, with a neutral detergent (for example, product name: Clean Ace, manufactured by AS ONE) and rinse it with ultrapure water. Then, 2 μL of ion-exchanged water is dropped as a liquid droplet, and the static contact angle of the liquid droplet is measured using the θ / 2 method 5 seconds later.

[0040] The static contact angle of water of the first functional part in the present invention is preferably 70° or less.

[0041] <Atomic Concentrations of Sulfur Atom (S), Phosphorus Atom (P), Nitrogen Atom (N), and Oxygen Atom (O) by XPS Measurement> The atomic concentration of the first functional part can be specified using X-ray photoelectron spectroscopy (XPS). As the XPS apparatus, K-ALPHA (manufactured by thermo scientific) can be used. By performing XPS measurement under the following condition 3, a Survey spectrum can be obtained.

[0042] [Condition 3] X-ray condition: Monochromatized AlKα ray, 30 W, 12 kV Analysis area: 200 μmφ Neutralization gun condition: 0.1 V, 200 μA Photoelectron extraction angle: 90° Time Per Step: 10 ms Sweep: 2 times Pass energy: 200 eV Survey energy range (step size): 0 eV - 1350 eV (0.1 eV) Inert gas species: Ar

[0043] The surface of the member is subjected to XPS measurement under the above condition 3, and a spectrum is obtained by performing a survey analysis. The concentrations of the detected sulfur atoms, nitrogen atoms, and phosphorus atoms can be calculated from the obtained spectrum, for example, using the data analysis software Avantage (Version 5, manufactured by Thermo Scientific). The obtained spectrum is charge-corrected with the C1s peak at 284.8 eV, and the peak area intensity is calculated after removing the background from the peaks based on the electron orbitals of the measured sulfur atoms, nitrogen atoms, and phosphorus atoms by the Shirley method, and then an analysis process is performed in which the peak area intensity is divided by the sensitivity coefficient specific to the device previously set in the data analysis software, and the atomic concentrations of the sulfur atoms, nitrogen atoms, and phosphorus atoms can be calculated.

[0044] In addition, in order to identify the interface between the first functional section and the second functional section described below, the concentration of oxygen atoms contained only in the first functional section, excluding the oxygen atoms contained in the oxide of the substrate, is calculated using the following formula. Oxygen atomic concentration (atm%) contained in the first functional part = total detected oxygen atomic concentration (atm%) - oxygen atomic concentration (atm%) contained in the base material The oxygen atom concentration in the substrate is expressed by the general formula M x O y The oxygen atom concentration of an oxide represented by the formula: Oxygen atomic concentration in the base material (atm%) = atomic concentration of detected element M (atm%) × y / x Here, the elements corresponding to M are Li, Be, Na, Ca, Mg, Ti, Cr, Mn, Fe, Co, Ni, Zn, Zr, Nb, Mo, Ag, Ba, Sr, Sn, Al, and Si, and x and y are determined by calculating the valence from the bond energy of the peak attributed to the detected M element.

[0045] The atomic concentration of one or more atoms selected from the group consisting of sulfur atoms, nitrogen atoms, phosphorus atoms, and oxygen atoms contained in the first functional portion is preferably 1.0 to 50.0 atm %, and more preferably 2.0 to 39.0 atm %.

[0046] <Calculation of the sputtering disappearance time (T1) of the first functional part by depth direction analysis of XPS> According to the above-mentioned condition 1, a spectrum is obtained by performing a Survey analysis every 5 seconds of the sputtering cycle. The concentration of each detected atom can be calculated from the obtained spectrum using, for example, data analysis software Avantage (Version 5, manufactured by Thermo Scientific). After charge correction with the C1s peak at 284.8 eV, the obtained spectrum is subjected to background removal by the Shirley method for the peaks based on the electron orbits of the measured atoms, and then the peak area intensity is calculated. An analysis process of dividing by the sensitivity coefficient specific to the apparatus preset in the data analysis software is performed to calculate the atomic concentrations of sulfur, nitrogen, and phosphorus, respectively, with all the detected atoms as the denominator, and the oxygen atom concentration excluding the oxygen atom concentration derived from the oxide contained in the substrate. The measurement point at which the atomic concentrations of sulfur, nitrogen, and phosphorus are 1.0 atm% or less and the oxygen atom concentration excluding the oxygen atom concentration derived from the oxide contained in the substrate is 6.0 atm% or less is defined as the midpoint (t1 seconds).

[0047] As shown in FIG. 4, the sputtering time T1 from the start point (0 seconds) to the midpoint (t1 seconds) is defined as the sputtering disappearance time of the first functional part. Since the sputtering disappearance time T1 of the first functional part is closely related to the film thickness of the first functional part, the sputtering disappearance time T1 of the first functional part can be used as a useful index for the film thickness of the first functional part.

[0048] The sputtering disappearance time (T1) of the first functional part in the present invention is 50 seconds or more and 1400 seconds or less, preferably 80 seconds or more and 1400 seconds or less, and more preferably 95 seconds or more and 1400 seconds or less.

[0049] <Identification of the second functional part> After reaching the midpoint (t1 seconds), the second functional part can be identified by performing XPS measurement of the peak spectrum of C1s according to the above-mentioned condition 2, and then performing XPS depth direction analysis in combination with sputtering according to the above-mentioned condition 1.

[0050] <Peak separation> The obtained C1s spectrum is subjected to peak separation using data analysis software Avantage (Version 5, Thermo Scientific). Peak separation refers to performing waveform separation on the basis of detected peaks in the overall waveform of the obtained spectrum, and identifying the bonding state of the carbon atom corresponding to each obtained waveform. This peak separation makes it possible to calculate the ratio of different bonding states even though it is the same element (carbon atom in the present invention). The details of the peak separation method are described below.

[0051] First, the obtained C1s peak is charge-corrected to 284.8 eV. In this state, peak separation is performed for the photoelectron spectrum of each of the types of bond states of the carbon atoms present in the C1s spectrum (hereinafter simply referred to as "bond types"), that is, the carbon atoms belonging to the CC bond, the carbon atoms belonging to the CO bond, and the carbon atoms belonging to the O=CO bond. A specific method for C1s peak separation will be described below.

[0052] First, in the range of 279.0 eV (start point) to 292.0 eV (end point) in the measurement range of C1s, the background of the peak is removed by the Shirley method. However, for the start point and end point, the average value of the intensity in the range of ±0.25 eV with each point as the median is taken as the background intensity at that point. For example, at the start point of C1s at 279.0 eV, the average value of the intensity in the range of ±0.25 eV of the median value of 279.0 eV, that is, the range of 278.75 eV to 279.25 eV, is taken as the background intensity at the start point. After that, the peak at 284.8 eV in the binding energy of C1s is assigned to a carbon atom having a C-C bond, the peak at 287.1 eV in the binding energy of C1s is assigned to a carbon atom having a C-O bond, and the peak at 289.2 eV in the binding energy of C1s is assigned to a carbon atom having an O=C-O bond, and the peaks are added. In addition, peaks suggested by the software are also added as necessary. The peak shape of the added peak shall follow a Gauss-Lorentz distribution. Then, fitting is performed using the peak fitting conditions below to obtain a spectrum for each bond type. If the fitting results do not meet the fitting completion criteria below, a peak is added at the position of the C1s binding energy that is the maximum among the positive maximum values ​​in the second derivative spectrum displayed on the screen, and fitting is performed again using the peak fitting conditions below. This operation is repeated until the fitting completion criteria below are met, at which point fitting is terminated. This completes the XPS peak separation.

[0053] [Peak fitting conditions] Fitting Algorithm:Powell Maximum Iterations: 500 Convergence:1e-05 Gauss-Lorentz Mix:Product [Fitting completion criteria] Normalised Chi Square≦10.0

[0054] <Calculation of the ratio of carbon atoms attributed to the C-C bond in the second functional part> In the above C1s spectrum, from the spectra of each bond type identified by peak separation of XPS, that is, carbon atoms attributed to the C-C bond, carbon atoms attributed to the C-O bond, and carbon atoms attributed to the O=C-O bond, the peak area intensity (Area Intensity) of carbon atoms attributed to each bond type is calculated using data analysis software Avantage (Version 5, manufactured by Thermo Scientific).

[0055] Next, the ratio of the peak area intensity of carbon atoms attributed to the C-C bond to the total of the peak area intensities of carbon atoms attributed to each bond type (hereinafter, also referred to as "the ratio of carbon atoms attributed to the C-C bond") is calculated in units of atm%. In the present invention, it is characterized in that the ratio of carbon atoms attributed to the C-C bond at the time of disappearance of the first functional part, that is, at the start of the second functional part, is 88 atm% or more and 100 atm% or less.

[0056] In the present invention, the ratio of carbon atoms attributed to the C-C bond at the start of the second functional part is preferably 91 atm% or more and 100 atm% or less, and more preferably 94 atm% or more and 100 atm% or less.

[0057] <Calculation of the sputter disappearance time (T2) of the second functional part by depth direction analysis of XPS> According to the above-mentioned condition 1, a spectrum is obtained by performing survey analysis every 5 seconds of the sputter cycle. The concentration of each detected atom can be calculated from the obtained spectrum, for example, using the data analysis software Avantage (Version 5, Thermo Scientific). The obtained spectrum is charge-corrected with the C1s peak at 284.8 eV, and the peak area intensity is calculated after removing the background from the peak based on the electron orbit of each measured atom by the Shirley method, and then an analysis process is performed in which the peak area intensity is divided by a sensitivity coefficient specific to the device that is preset in the data analysis software. After reaching the midpoint (t1 second), an XPS depth profile analysis is performed according to condition 1, and the measurement point where the carbon atom concentration becomes 2.5 atm% or less is set as the end point (t2 second).

[0058] As shown in Fig. 4, the sputtering time T2 (t2-t1) from the midpoint (t1 seconds) to the end point (t2 seconds) is defined as the sputtering disappearance time of the second functional part. Since the sputtering disappearance time (t) of the second functional part is closely related to the film thickness and density of the second functional part, the sputtering disappearance time (T2) of the second functional part can be used as a useful index of the film thickness and density of the second functional part.

[0059] The sputter disappearance time (T2) of the second functional portion in the present invention is from 105 seconds to 360 seconds, preferably from 130 seconds to 360 seconds, and more preferably from 130 seconds to 310 seconds.

[0060] Manufacturing method of components The method for producing the member 10 of the present invention includes the steps of preparing a substrate 3, forming a second functional portion 2, and forming a first functional portion 1.

[0061] A process of preparing a substrate Prepare the base material 3. The base material 3 is as already described.

[0062] <Cleaning of substrate> The substrate is preferably washed to make its surface clean. For example, the substrate is preferably washed with a neutral detergent and rinsed with ion-exchanged water or ultrapure water. Any water droplets remaining on the substrate surface are preferably dried using an air blower or a dryer.

[0063] <Activation treatment of substrate surface> In order to form the second functional portion, it is preferable to perform an activation treatment on the surface of the base material. After cleaning the substrate surface, in order to activate the hydroxyl groups present on the substrate surface, a surface activation treatment may be performed using UV, atmospheric pressure plasma, alkaline ultrasonic cleaning, ceria powder polishing, etc. By performing the activation treatment, a strong bond is formed between the substrate and the second functional part.

[0064] Step of forming a second functional portion The process of forming the second functional part preferably includes a process of preparing a composition for forming the second functional part (hereinafter referred to as a "reaction solution"), a process of contacting the reaction solution with the substrate surface, a post-cleaning process, and a heating and drying process.

[0065] <Step of preparing reaction solution> The step of preparing the reaction solution is a step of dissolving the raw material forming the second functional part in a solvent. For example, the reaction solution can be prepared by preparing a solvent in a container such as a glass bottle, and dissolving the raw material in the solvent while stirring. After dissolving the raw material, in order to homogenously form the second functional part, it is preferable to add a step of stirring with ultrasonic waves for 1 minute to increase the dispersibility of the raw material in the solvent.

[0066] <Raw material for forming the second functional part> The raw material for forming the second functional part is preferably a coupling agent. As the coupling agent, an alkylsilane compound having a binding functional group 23, which is represented by the following formula 1 and serves as a starting point for forming the first functional part, is preferable.

[0067] [ka]

[0068] When the substrate is a metal oxide mainly composed of Si such as glass, it is preferable to use an alkylsilane as the coupling agent. In the above formula 1, the groups R1 to R3 may each independently be selected from methoxy, ethoxy, propoxy, isopropoxy, and halogen (particularly chlorine and bromine). (R1, R2, R3)Si- is a functional group capable of bonding to the metal oxide. n is an integer of 11 to 29, preferably an integer of 22 to 28. R4 is a bonding functional group, specifically, a functional group capable of bonding to the first functional part by atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer (RAFT) polymerization, thermal polymerization, photopolymerization, or a coupling reaction. More specifically, it is preferably an acryloyl group, methacryloyl group, vinyl group, allyl group, styryl group, mercapto group, isocyanate group, epoxy group, amino group, etc. The bonding functional group is preferably a bonding functional group particularly selected from the group represented by the following formula 2. In formula 2, X is a halogen element, preferably a bromine atom or a chlorine atom.

[0069]

Chemical formula

[0070] <Raw materials for forming the mixed dense film> As already described, the molecule constituting the second functional part is preferably a mixture of a linear alkylsilane having a bonding functional group represented by formula 1 and a linear alkylsilane having no bonding functional group represented by the following formula 3. The number of carbon atoms of the alkyl group in the main chain of the raw material molecule having no bonding functional group is preferably about the same as the number of carbon atoms of the alkyl group in the main chain of the raw material molecule having a bonding functional group. Preferably, the difference in the number of carbon atoms is 0 or more and 5 or less. It is more preferable that the number of carbon atoms of the linear alkylsilane having a bonding functional group is large. The groups R5 to R7 may each independently be selected from methoxy, ethoxy, propoxy, isopropoxy, and halogen (particularly chlorine and bromine). m is an integer of 8 to 27. It is preferable to satisfy m < n.

[0071] [ka]

[0072] <Solvent> Examples of the solvent include, but are not limited to, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, halogen-based solvents such as toluene, chloroform, and dichloromethane, and water. If necessary, a mixture of two or more types of solvents may be used. When the groups R1 to R3 and the groups R5 to R7 are alkoxides, the pH may be adjusted by dropping an acid-base catalyst such as hydrochloric acid, acetic acid, or aqueous ammonia to promote hydrolysis of the alkoxide.

[0073] <Step of applying the reaction solution to the substrate> After washing the substrate, a reaction solution containing the raw material is applied to the substrate. The method of applying the solution to the substrate is not particularly limited, but examples thereof include an immersion method in which the substrate is immersed in the reaction solution, a coating method by spraying or wiping, and a mist method in which the substrate is contacted with a mist of the reaction solution. Preferably, the second functional part is formed on the surface of the substrate by an immersion method in which the substrate is immersed in the reaction solution.

[0074] <Temperature and application time of the reaction solution applied to the substrate> The temperature and application time when applying the reaction solution to the substrate vary depending on the type of substrate and raw material, but generally, the temperature is preferably 0° C. to 60° C., and the application time is preferably 1 minute to 48 hours. By extending the application time, a dense ultra-thin film containing hydrophobic groups is formed, and the reaction proceeds.

[0075] <Post-cleaning process after forming the second functional part> Post-cleaning may be performed in some cases. There is no limitation on the method of post-cleaning, and it may be performed by a general method such as rinsing with ultrapure water or alcohol, wiping, ultrasonic cleaning, etc. Preferably, ultrasonic cleaning is repeated twice for 5 minutes in an ethanol solution, and the substrate surface is rinsed with ultrapure water.

[0076] <Heat drying process> After the step of applying the reaction solution to the substrate, it is preferable to heat and dry the substrate. By doing so, the bonding between the silyl group of the raw material molecules forming the second functional part and the substrate containing the metal oxide is promoted, and the adhesion (such as water resistance, chemical resistance, and abrasion resistance) of the second functional part is improved.

[0077] <Temperature and time of the heat drying process> The temperature and time of the heat drying process vary depending on the type of the substrate and the raw material, but generally, the temperature is preferably 40°C or higher and 200°C or lower, and the time is preferably 1 minute or longer and 48 hours or shorter.

[0078] Step of forming a first functional portion The step of forming the first functional part is to apply a composition containing a compound having a hydrophilic group (hereinafter referred to as "polymerization solution") to the surface of the second functional part. It is preferable that the compound having a hydrophilic group further has a reactive functional group capable of reacting with the bonding functional group contained in the second functional part. Specifically, it is preferable to form a hydrophilic first functional part by chemically bonding a raw material having a hydrophilic group to the bonding functional group contained in the second functional part by atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer (RAFT) polymerization, or polymerization (or coupling) reaction by light or heat. It is more preferable to form the first functional part by atom transfer radical polymerization (ATRP). Thereby, it becomes possible to form a first functional part with a thick film and a narrow molecular weight distribution, and it becomes possible to uniformly exhibit high hydrophilicity.

[0079] <Atom transfer radical polymerization (ATRP)> It is preferable to apply a polymerization solution in which a raw material having a hydrophilic group, a solvent, a metal salt for ATRP catalyst, a ligand for ATRP catalyst, and a reducing agent are mixed at an arbitrary ratio to the surface of the second functional part, and polymerize the compound having a hydrophilic group to form a hydrophilic first functional part. The ATRP process is preferably composed of a process of preparing a polymerization solution, a process of applying the polymerization solution, and a post-washing process.

[0080] <Preparation of the polymerization solution for ATRP> Mix a raw material having a hydrophilic group, a solvent, a metal salt for an ATRP catalyst, a ligand for an ATRP catalyst, and a reducing agent in any ratio.

[0081] <Raw material having a hydrophilic group for ATRP> The raw material having a hydrophilic group preferably has a reactive functional group capable of reacting with the binding functional group contained in the second functional part, and further contains a compound having one or more of the hydrophilic groups already described. The reactive functional group may be, for example, at least one selected from an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, and a styryl group. Specifically, trimethyl-2-methacryloyloxyethylammonium chloride, potassium 3-(methacryloyloxy)propanesulfonate, 2-(methacryloyloxy)ethanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, potassium 3-(acryloyloxy)propane-1-sulfonate, potassium 2-(acryloyloxy)ethane-1-sulfonate, sodium p-styrenesulfonate, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, [3-(methacryloylamino)propyl]dimethyl(3-sulfobutyl)ammonium hydroxide, 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propanate, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, sodium 2-aminoethylsulfonate, potassium 2-aminoethylsulfonate, 2-hydroxyethyl methacrylate, N-(2-hydroxyethyl)acrylamide, polyethylene glycol monomethyl ether methacrylate, methacryloylcholine chloride, and the like can be mentioned.

[0082] <Metal salt for ATRP catalyst> As the metal salt for the ATRP catalyst, it is not particularly limited as long as it can be reduced by a reducing agent contained in the polymerization solution after oxidation or by itself. Examples include copper(I) chloride, copper(II) chloride, copper(I) bromide, copper(II) bromide, titanium(II) chloride, titanium(III) chloride, titanium(IV) chloride, titanium(IV) bromide, iron(II) chloride, iron(III) chloride, iron(II) bromide, iron(III) bromide, cobalt(II) chloride, cobalt(II) bromide, nickel(II) chloride, nickel(II) bromide, molybdenum(III) chloride, molybdenum(V) chloride, ruthenium(III) chloride, etc.

[0083] <Ligand for ATRP catalyst> The ligand for the ATRP catalyst is not particularly limited. Examples include 2,2'-bipyridyl, 4,4'-dimethyl-2,2'-bipyridyl, 4,4'-di-t-butyl-2,2'-bipyridyl, 4,4'-dinonyl-2,2'-bipyridyl, N-butyl-2-pyridylmethanimine, N-octyl-2-pyridylmethanimine, N-dodecyl-N-(2-pyridylmethylene)amine, N-octadecyl-N-(2-pyridylmethylene)amine, N,N,N',N'',N'''-pentamethyldiethylenetriamine, tris(2-pyridylmethyl)amine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, tris(2-dimethylaminoethyl)amine, 1,4,8,11-tetraazacyclotetradecane, 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane, N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine, etc.

[0084] <Reducing agent> The reducing agent is not particularly limited. Examples include ascorbic acid, glucose, di-n-butyltin bis(2-ethylhexanoate), etc. Among them, ascorbic acid is preferred because it has a small environmental impact and shows a strong reducing effect.

[0085] <Solvent for the polymerization solution for ATRP polymerization> Examples of the solvent for the polymerization solution forming the first functional part include, but are not limited to, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, and water. The solvents may be used as a mixture of multiple types as needed. It is preferably a solvent in which a compound having a hydrophilic group, a metal salt for an ATRP catalyst, a ligand for an ATRP catalyst, and a reducing agent are dissolved.

[0086] <Step of applying the polymerization solution> After forming the second functional part, the polymerization solution is applied to the surface of the second functional part formed on the substrate surface. During the application, the polymerization reaction proceeds. There is no limitation on the method of applying the polymerization solution to the surface of the second functional part. For example, it can be carried out by common coating methods such as brush coating, spray coating, dip coating, spin coating, curtain coating, bar coating, or by immersion.

[0087] <Temperature and application time during application> The temperature and application time when applying the polymerization solution to the substrate having the second functional part formed on its surface vary depending on the type of the substrate and the polymerization solution. Generally, the temperature is preferably 0°C or higher and 60°C or lower, and the time is preferably 1 minute or longer and 24 hours or shorter.

[0088] <Treatment during application> During the application of the polymerization solution, in order to prevent the polymerization solution from being oxidized by oxygen in the air, it is preferably to perform a treatment such that the polymerization solution does not come into contact with the air as much as possible. There is no limitation on the treatment method, but it is more preferable to perform a treatment of covering the substrate with a glass plate, wrap, film, etc. after applying the polymerization solution.

[0089] <Post-washing step after ATRP polymerization> There is no limitation on the post-washing method, and it may be carried out by common methods such as rinsing with ultrapure water or alcohol, wiping, and ultrasonic cleaning. It is preferable to repeat ultrasonic cleaning in an ethanol solution for 5 minutes twice and then rinse the substrate surface with ultrapure water.

[0090] <Polymerization (or coupling) reaction by light and heat> It is preferable to form the first functional part by applying a polymerization solution containing a raw material having a hydrophilic group, which is dissolved in a solvent and a radical polymerization initiator, and reacting the binding functional group of the second functional part with the reactive functional group of the raw material molecule having a hydrophilic group by radicals generated from the radical polymerization initiator by light or heat. This process is composed of a process of preparing a polymerization solution, a process of applying the prepared polymerization solution to the surface of the second functional part formed on the surface of the substrate, a polymerization process by UV irradiation or heating, and a post-cleaning process.

[0091] <Step of preparing polymerization solution> A raw material having a hydrophilic group and a radical polymerization initiator are dissolved in a solvent in an arbitrary ratio.

[0092] <Raw materials with hydrophilic groups for photo- and thermal polymerization> The raw material having a hydrophilic group has a reactive functional group that reacts with the binding functional group contained in the second functional part, and preferably further contains one or more of the hydrophilic groups already described. The element that can constitute the hydrophilic group is preferably at least one selected from sulfur, phosphorus, nitrogen, and oxygen atoms. The reactive functional group may be at least one selected from an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, a styryl group, a mercapto group, an isocyanate group, an epoxy group, an amino group, and an alcohol group. Specifically, trimethyl-2-methacryloyloxyethyl ammonium chloride, potassium 3-(methacryloyloxy)propanesulfonate, 2-(methacryloyloxy)ethanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, potassium 3-(acryloyloxy)propane-1-sulfonate, potassium 2-(acryloyloxy)ethane-1-sulfonate, sodium p-styrenesulfonate, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, [3-(methacryloylamino)propyl]dimethyl(3-sulfobutyl)ammonium hydroxide, 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid, 3-[[ 2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetic acid, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl]phosphate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propanoate, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, sodium 2-aminoethylsulfonate, potassium 2-aminoethylsulfonate, sodium 4-aminobenzenesulfonate, sodium 2-hydroxyethylsulfonate, sodium 3-mercapto-1-propanesulfonate Examples of suitable amines include thorium, sodium 2-glycidylethylsulfonate, sodium aminosulfonate, potassium aminosulfonate, aminomethanesulfonic acid, 3-aminopropanesulfonic acid, 2-aminobenzenesulfonic acid, 4-aminobenzenesulfonic acid, 1-amino-2-naphthol-4-sulfonic acid, 6-amino-4-hydroxy-2-naphthalenesulfonic acid, sodium hydroxymethanesulfonate, 4-hydroxy-1-butanesulfonic acid, 2-hydroxyethyl methacrylate, N-(2-hydroxyethyl)acrylamide, polyethylene glycol monomethyl ether methacrylate, and methacryloylcholine chloride.

[0093] <Radical polymerization initiator> The radical polymerization initiator is a compound that decomposes by light or heat to generate radicals. The radical polymerization initiator is classified into a photoradical polymerization initiator that decomposes by light and a thermal radical polymerization initiator that decomposes by heat. The radical polymerization initiator is preferably water-soluble. As the photoradical polymerization initiator, benzophenone, 1-hydroxy-cyclohexyl-phenyl-ketone, a mixture of 1-hydroxy-cyclohexyl-phenyl-ketone and benzophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 2-hydroxy-1-[4-{4-(2-hydroxy-2-methyl-propionyl)-benzyl}phenyl]-2-methyl-1-propan-1-one, oxyphenylacetic acid, a mixture of 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester and oxyphenylacetic acid, 2-(2-hydroxyethoxy)ethyl ester, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like are preferred.

[0094] <Solvent for photo- and thermal polymerization> Examples of the solvent for the polymerization solution include, but are not limited to, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, and water. If necessary, a mixture of multiple types of solvents may be used.

[0095] <Step of applying polymerization solution> After the second functional part is formed, the polymerization solution is applied to the surface of the second functional part formed on the substrate surface. The method of applying the polymerization solution to the surface of the second functional part is not limited, and it can be performed by a general application method such as brush coating, spray coating, dip coating, spin coating, curtain coating, bar coating, etc.

[0096] <Temperature when applied> The temperature at which the polymerization solution is applied to the substrate having the second functional part formed on its surface varies depending on the type of substrate and polymerization solution, but generally the temperature is preferably 0°C or higher and 60°C or lower, and the time is preferably 1 minute or higher and 24 hours or lower.

[0097] <Polymerization process> In order to promote the polymerization reaction, it is preferable to irradiate with ultraviolet light or heat. As a device for irradiating ultraviolet light, a high pressure mercury lamp, a metal halide lamp, an ultraviolet LED (UV-LED) lamp having an emission wavelength of a peak wavelength of 405 nm or less, etc. can be used alone or in combination. In addition, as a device for generating heat, an electric oven, a hot air dryer, an infrared ray irradiator, etc. can be used.

[0098] <Polymerization process temperature and time> The temperature and time of the polymerization step vary depending on the type of substrate and polymerization solution, but in general, the temperature is preferably 0° C. or higher and 200° C. or lower, and the time is preferably 1 minute or higher and 24 hours or lower.

[0099] <Post-cleaning process> There is no limitation on the method of post-cleaning, and it may be performed by a general method such as rinsing with ultrapure water or alcohol, wiping, ultrasonic cleaning, etc. It is preferable to repeat ultrasonic cleaning in an ethanol solution for 5 minutes twice, and then rinse the surface of the substrate with ultrapure water. EXAMPLES

[0100] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to these examples.

[0101] Base material As the substrate, a 50 mm square soda lime glass (Ikeda Glass soda lime glass product number FL5; hereinafter referred to as "glass") was used. In addition, as the substrate, the following sanitary ware was used.

[0102] The sanitary ware was produced in the following manner.

[0103] <Preparation of the base material for sanitary ware> A sanitary ware slip prepared from raw materials such as silica sand, feldspar, limestone, and clay was cast into a plaster mold to obtain a molded body. This molded body was then dried. The dried molded body was fired in the firing process described below to produce the base material for the sanitary ware.

[0104] <Preparation of glaze> A number of glaze raw materials having the compositions shown in the following table in terms of oxides were prepared. 600 g of each glaze raw material, 400 g of water, and 1 kg of alumina balls were placed in a 2-liter ceramic pot and ground in a ball mill for about 65 hours to obtain glazes.

[0105] [Table 1]

[0106] Glaze was applied to the dried molded body by spray coating and fired at 1100-1200℃ to produce sanitary ware with a glaze layer formed, which was then cut into 30mm square pieces. In addition, dirt on the surface of the glaze layer was removed and the hydroxyl groups on the surface were activated.

[0107] A second functional portion and a first functional portion were formed in the above sanitary ware by the procedure described below, to obtain the sanitary ware of Example 5 below.

[0108] A second functional portion and a first functional portion were formed on the above glass by the procedure described below, to obtain members of Examples 1 to 4, 6 to 10, Comparative Examples 1 to 3, and Reference Example 1 described below.

[0109] Example 1 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> 13 mg of (11-(2-bromo-2-methyl)propionyloxy)undecyltrichlorosilane and 25 mg of decyltrichlorosilane were dissolved in 30 mL of toluene to prepare a coupling solution. The substrate was placed in a sample bottle, and the coupling solution was added so that the substrate was completely immersed, and the bottle was then covered and reacted at room temperature for 16 hours. The substrate was then removed from the sample bottle, washed with ethanol, and dried using an air blower. In this way, a second functional portion was formed on the substrate surface.

[0110] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 0.45 g of potassium 3-(methacryloyloxy)propanesulfonate was dissolved in the obtained solution and stirred for 1 minute, after which 2.5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered from above with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 1 hour. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0111] Example 2 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0112] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 0.55 g of potassium 3-(methacryloyloxy)propanesulfonate was dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered from above with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 3 hours. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0113] Example 3 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0114] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 4.4 g of potassium 3-(methacryloyloxy)propanesulfonate was dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered from above with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 3 hours. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0115] Example 4 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> A solvent was prepared by mixing 93 mL of ethanol and 7 mL of 10% aqueous ammonia. 20 mg of 23-(triethoxysilyl) 2-bromo-2-methylpropanate was dissolved in 30 mL of this solvent and stirred for 1 hour in an environment of 40°C to prepare a coupling solution. The substrate was placed in a sample bottle, and the coupling solution was added so that the substrate was completely immersed, and the bottle was closed and reacted at room temperature for 16 hours. The substrate was then removed from the sample bottle, washed with ethanol, and dried using an air blower. In this way, a second functional part was formed on the substrate surface.

[0116] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> Using the same procedure as in step 2 of Example 1, a first functional portion was formed on the surface of the second functional portion.

[0117] Example 5 Sanitary ware was used as the base material. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> A solvent was prepared by mixing 93 mL of ethanol and 7 mL of 10% aqueous ammonia. 20 mg of 23-(triethoxysilyl) 2-bromo-2-methylpropanate and 37 mg of octadecyltriethoxysilane were dissolved in 30 mL of this solvent and stirred for 1 hour in a 40°C environment to prepare a coupling solution. The substrate was placed in a sample bottle, and the coupling solution was added so that the substrate was completely immersed, and the bottle was closed and reacted at room temperature for 16 hours. The substrate was then removed from the sample bottle, washed with ethanol, and dried using an air blower. In this way, a second functional part was formed on the substrate surface.

[0118] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> Using the same procedure as in step 2 of Example 1, a first functional portion was formed on the surface of the second functional portion.

[0119] Example 6 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> A solvent was prepared by mixing 93 mL of ethanol and 7 mL of 10% aqueous ammonia. 20 mg of 23-(triethoxysilyl) 2-bromo-2-methylpropanate and 43 mg of octadecyltriethoxysilane were dissolved in 30 mL of this solvent and stirred for 1 hour in a 40°C environment to prepare a coupling solution. The substrate was placed in a sample bottle, and the coupling solution was added so that the substrate was completely immersed, and the bottle was closed and reacted at room temperature for 16 hours. The substrate was then removed from the sample bottle, washed with ethanol, and dried using an air blower. In this way, a second functional part was formed on the substrate surface.

[0120] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> Using the same procedure as in step 2 of Example 2, a first functional portion was formed on the surface of the second functional portion.

[0121] Example 7 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0122] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 0.82 g of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid was dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered from above with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 1 hour. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0123] Example 8 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0124] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 23 μL of N-(2-hydroxyethyl)acrylamide was dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 1 hour. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0125] Example 9 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0126] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.6 mg of copper (II) bromide and 10.9 mg of 2,2'-bipyridyl were dissolved in 6.8 mL of ultrapure water and stirred for 1 minute. 1.2 mL of methacryloylcholine chloride (80% aqueous solution) was dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered from above with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 3 hours. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0127] <Functional ultra-thin film made by mixing a compound with an anionic hydrophilic group and a compound with a zwitterionic hydrophilic group> Example 10 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0128] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 1.6 g of potassium 3-(methacryloyloxy)propanesulfonate and 0.48 g of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid were dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and the surface was covered with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 1 hour. The substrate was then taken out and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0129] Comparative Example 1 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> 15 mg of 3-(triethoxysilyl)propyl isocyanate and 30 mL of 1-methoxy-2-propanol were mixed and stirred at room temperature, and then 15 mg of 3% aqueous hydrochloric acid was added and stirred for 30 minutes to carry out hydrolysis, preparing a reaction solution. The resulting reaction solution was applied to the surface of the substrate, placed in a drying oven, and left to stand at 60°C for 30 minutes. Thereafter, the substrate with the second functional part formed on its surface was taken out, rinsed with ethanol and ultrapure water, and dried using an air blower. In this way, the second functional part was formed on the surface of the substrate.

[0130] <Step 2: Formation of the first functional part on the surface of the second functional part (by amine addition reaction)> 38 g of 2-aminoethylsulfonic acid, 12 g of sodium hydroxide, and 50 g of ion-exchanged water were stirred at room temperature of 25°C for about 1 hour to obtain an aqueous solution of sodium 2-aminoethylsulfonate. 10 g of urea and 10 g of isopropyl alcohol were added to this aqueous solution and stirred until it became a transparent homogeneous solution. The obtained solution was applied to the surface of the second functional part obtained in step 1, placed in a drying furnace, and left to stand at 60°C for 30 minutes. Thereafter, the substrate with the first functional part formed on the surface of the second functional part was taken out, washed with ethanol and ultrapure water, and dried using an air blower.

[0131] Comparative Example 2 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> A coupling solution was prepared by dissolving 54 mg of (11-(2-bromo-2-methyl)propionyloxy)undecyltrichlorosilane in 30 mL of toluene. The substrate was placed in a sample bottle, and the coupling solution was added so that the substrate was completely immersed. The bottle was then covered and reacted at room temperature for 16 hours. The substrate was then removed from the sample bottle, washed with ethanol, and dried using an air blower. The substrate was then left to stand at 120°C for 30 minutes in a drying oven, rinsed with ethanol and ultrapure water, and dried using an air blower. In this way, a second functional part was formed on the substrate surface.

[0132] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> Using the same procedure as in step 2 of Example 1, a first functional portion was formed on the surface of the second functional portion.

[0133] Comparative Example 3 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> Using the same procedure as in step 1 of Example 1, a second functional portion was formed on the surface of the base material.

[0134] <Step 2: Formation of the first functional part on the surface of the second functional part (by living radical polymerization)> 1.7 mg of copper(II) chloride and 5 μL of N,N,N',N'',N''-pentamethyldiethylenetriamine were dissolved in 8.00 mL of ultrapure water and stirred for 1 minute. 0.35 g of potassium 3-(methacryloyloxy)propanesulfonate was dissolved in the obtained solution and stirred for 1 minute, after which 5 mg of ascorbic acid was added and stirred for 2 minutes to prepare a polymerization solution. 400 μL of this polymerization solution was dropped onto the surface of the second functional part obtained in step 1, and covered from above with a glass plate of the same size as the substrate so that the polymerization solution and the substrate were in uniform contact with each other, and the solution was left to stand for 1 hour. The substrate was then removed and washed with ultrapure water. In this way, the first functional part was formed on the surface of the second functional part.

[0135] Reference example 1 Glass was used as the substrate. <Step 1: Formation of the second functional part on the surface of the substrate (silane coupling treatment of the surface of the substrate)> A coupling solution was prepared by dissolving 64 mg of triacontyltrichlorosilane in 30 mL of toluene. The substrate was placed in a sample bottle, and the coupling solution was added so that the substrate was completely immersed. The bottle was then covered and reacted at room temperature for 16 hours. The substrate was then removed from the sample bottle, washed with ethanol, and dried using an air blower. In this way, a component having only the second functional portion formed on the substrate surface was obtained.

[0136] Analysis and Evaluation The members produced as described above (Examples 1 to 10, Comparative Examples 1 to 3, and Reference Example 1) were subjected to the following analysis and evaluation.

[0137] <Cleaning of components> Before XPS measurement, the surface of the component was cleaned. A neutral detergent (product name: Clean Ace, manufactured by AS ONE) and a urethane sponge were used for cleaning. The urethane sponge used was a urethane sponge layer of "Scotch-Brite" ("Bath Shine" antibacterial sponge, no abrasive particles, manufactured by 3M Japan, BM-22K; "Scotch-Brite" and "Bath Shine" are registered trademarks of 3M Company) cut into a 2 cm cube. The urethane sponge was soaked in water, and after lathering with a neutral detergent, the sponge was pressed against the surface of the first functional part with a load of about 100 g / cm2 and washed by moving it back and forth five times. After that, it was thoroughly rinsed with ultrapure water.

[0138] <Identification of the first functional part> The first functional portion was identified by the XPS measurement under the above-mentioned condition 3 and the XPS depth profile analysis under the above-mentioned condition 1. K-ALPHA (manufactured by Thermo Scientific) was used as the XPS device.

[0139] XPS measurements <Concentrations of sulfur atoms (S), phosphorus atoms (P), nitrogen atoms (N) and oxygen atoms (O) in the first functional part> The atomic concentration of the first functional part was measured by X-ray photoelectron spectroscopy (XPS). A survey spectrum was obtained by performing XPS measurement under the above-mentioned condition 3. The concentration of the detected atoms was calculated from the obtained spectrum using data analysis software Avantage (Version 5, manufactured by Thermo Scientific). The obtained spectrum was charge-corrected with the C1s peak set at 284.8 eV, and the peak area intensity was calculated after removing the background from the peak based on the electron orbit of each measured atom by the Shirley method, and an analysis process was performed in which the peak area intensity was divided by a sensitivity coefficient specific to the device previously set in the data analysis software, and the atomic concentration of sulfur, nitrogen, and phosphorus was calculated using the total number of detected atoms as a modulus, and the oxygen atomic concentration excluding the oxygen atomic concentration derived from the oxide contained in the substrate was calculated. Here, in Examples 1 to 6 and Comparative Examples 1 to 3, the atomic concentration of sulfur contained in sulfonic acid groups was measured, in Examples 7 and 9, the atomic concentration of nitrogen contained in quaternary ammonium groups was measured, in Example 8, the atomic concentration of nitrogen contained in amide bonds was measured, and in Example 10, the atomic concentration of sulfur contained in anionic and amphoteric sulfonic acid groups and the atomic concentration of nitrogen contained in amphoteric quaternary ammonium groups were measured. The calculated sulfur and nitrogen atomic concentrations are shown in Table 2.

[0140] <Calculation of the time (T1) for the sputter disappearance of the first functional part> XPS depth profile analysis was performed under condition 1. First, a spectrum was obtained by performing survey analysis every 5 seconds of the sputter cycle. The concentration of the detected atoms was calculated from the obtained spectrum using data analysis software Avantage (Version 5, Thermo Scientific). The obtained spectrum was charge-corrected with the C1s peak at 284.8 eV, and the peak area intensity was calculated after removing the background from the peak based on the electron orbit of each measured atom by the Shirley method, and an analysis process was performed in which the peak area intensity was divided by a sensitivity coefficient specific to the device previously set in the data analysis software, and the atomic concentration of sulfur, nitrogen, and phosphorus was calculated using the total number of detected atoms as a modulus, and the oxygen atomic concentration excluding the oxygen atomic concentration derived from the oxide contained in the substrate was calculated. The measurement point where the atomic concentration of sulfur, nitrogen, and phosphorus was 1.0 atm% and the oxygen atomic concentration excluding the oxygen atomic concentration derived from oxides contained in the substrate was 6.0% or less was set as the midpoint (t1 seconds), and the sputtering time from the start point (0 seconds) to the midpoint (t1 seconds) was calculated as the sputter disappearance time T1 (t1-0) of the first functional part. The results are shown in Table 2.

[0141] <Identification of the second functional part> The second functional portion was identified by the XPS measurement under the above-mentioned condition 2 and the XPS depth profile analysis under the above-mentioned condition 1. K-ALPHA (manufactured by Thermo Scientific) was used as the XPS device.

[0142] First, a spectrum was obtained by performing survey analysis every 5 seconds of the sputter cycle under the above-mentioned condition 1. The concentration of the detected atoms was calculated from the obtained spectrum using the data analysis software Avantage (Version 5, manufactured by Thermo Scientific). The obtained spectrum was charge-corrected with the C1s peak set at 284.8 eV, and the peak area intensity was calculated after removing the background from the peak based on the electron orbit of each measured atom by the Shirely method, and an analysis process was performed in which the peak area intensity was divided by a sensitivity coefficient specific to the device previously set in the data analysis software, and the atomic concentration of sulfur, nitrogen, and phosphorus was calculated using the total number of detected atoms as a parameter, and the oxygen atomic concentration excluding the oxygen atomic concentration derived from the oxide contained in the substrate was calculated. At the measurement point (t1 seconds) when the atomic concentrations of sulfur, nitrogen, and phosphorus were 1.0 atm% or less and the oxygen atomic concentration excluding the oxygen atomic concentration derived from oxides contained in the substrate was 6.0% or less, that is, the point at which it was deemed that the first functional part had disappeared due to sputtering, a scan analysis was performed in the above energy range (279.0 eV-292.0 eV) to obtain a C1s peak spectrum of the second functional part.

[0143] <Peak separation> The obtained C1s spectrum was subjected to peak separation using data analysis software Avantage (Version 5, Thermo Scientific). First, the obtained C1s peak was charge-corrected to 284.8 eV. In this state, peak separation was performed for the photoelectron spectra of the types of bond states of the carbon atoms present in the C1s spectrum (hereinafter simply referred to as "bond types"), that is, the carbon atoms belonging to CC bonds, the carbon atoms belonging to CO bonds, and the carbon atoms belonging to O=CO bonds. A specific method for C1s peak separation will be described below.

[0144] First, the background of the peak was removed by the Shirley method in the range of 279.0 eV (start point) to 292.0 eV (end point) in the measurement range of C1s. However, for the start point and end point, the average value of the intensity in the range of ±0.25 eV with each point as the median was used as the background intensity at that point. For example, at the start point of C1s at 279.0 eV, the average value of the intensity in the range of ±0.25 eV of the median value of 279.0 eV, that is, the range of 278.75 eV to 279.25 eV, was used as the background intensity at the start point. After that, the peak at 284.8 eV in the binding energy of C1s was assigned to a carbon atom attributable to a CC bond, the peak at 287.1 eV in the binding energy of C1s was assigned to a carbon atom attributable to a CO bond, and the peak at 289.2 eV in the binding energy of C1s was assigned to a carbon atom attributable to an O=CO bond, and the peaks were added. In addition, peaks suggested by the software were also added as necessary. The peak shape of the added peak was assumed to follow a Gauss-Lorentz distribution. After that, fitting was performed using the peak fitting conditions below to obtain spectra for each bond type. If the fitting results did not meet the fitting completion criteria below, a peak was added at the position of the C1s binding energy that had the maximum value among the positive maxima in the second derivative spectrum displayed on the screen, and fitting was performed again using the peak fitting conditions below. This operation was repeated until the fitting completion criteria below were met, and fitting was completed once. This completed the XPS peak separation.

[0145] [Peak fitting conditions] Fitting Algorithm:Powell Maximum Iterations: 500 Convergence:1e-05 Gauss-Lorentz Mix:Product [Fitting completion criteria] Normalised Chi Square≦10.0

[0146] <Calculation of the ratio of carbon atoms belonging to CC bonds in the second functional part> In the above C1s spectrum, the peak area intensity of the carbon atoms assigned to each bond type identified by XPS peak separation, i.e., the carbon atoms assigned to the C-C bond, the carbon atoms assigned to the C-O bond, and the carbon atoms assigned to the O=C-O bond, was calculated using the data analysis software Avantage (Version 5, Thermo Scientific).

[0147] Next, the ratio of the peak area intensity of carbon atoms attributable to C-C bonds to the total peak area intensities of carbon atoms attributable to each bond type (hereinafter also referred to as "the ratio of carbon atoms attributable to C-C bonds") was calculated in atm%. Table 2 shows the proportion of carbon atoms belonging to CC bonds when the first functional portion disappears, that is, at the start point of the second functional portion.

[0148] <Calculation of the time (T2) for the sputter disappearance of the second functional part> According to the above-mentioned condition 1, a spectrum was obtained by performing a survey analysis every 5 seconds of the sputtering cycle. The concentration of each detected atom was calculated from the obtained spectrum using the data analysis software Avantage (Version 5, Thermo Scientific). The obtained spectrum was charge-corrected with the C1s peak at 284.8 eV, and the peak area intensity was calculated after removing the background by the Shirley method for the peak based on the electron orbit of each measured atom, and an analysis process was performed in which the peak area intensity was divided by a sensitivity coefficient specific to the device previously set in the data analysis software, and the atomic concentrations of sulfur, nitrogen, and phosphorus, and the oxygen atomic concentration excluding the oxygen atomic concentration derived from the oxide contained in the substrate, were calculated using the total detected atoms as a parameter. The measurement point at which the atomic concentrations of sulfur, nitrogen, and phosphorus were 1.0 atm% or less and the oxygen atomic concentration excluding the oxygen atomic concentration derived from the oxide contained in the substrate was 6.0 atm% or less was set as the midpoint (t1 second), and the measurement point at which the carbon atom concentration was 2.5 atm% or less was set as the end point (t2 second). In this way, the sputtering time T2 (t2-t1) from the midpoint (t1 seconds) to the end point (t2 seconds) was calculated as the sputter disappearance time of the second functional part. The results are shown in Table 2.

[0149] Water contact angle on the surface of the component The contact angle of water on the surface of each component was measured. Immediately before the measurement, the surface of each component was washed with a neutral detergent (Clean Ace) and rinsed with ultrapure water. Then, 2 μL of ion-exchanged water was dropped onto the surface of each component, and the static contact angle of the droplet was measured after 5 seconds. A contact angle meter (model number: DMs-401, manufactured by Kyowa Interface Science Co., Ltd.) was used to measure the contact angle, and the static contact angle was obtained by the θ / 2 method. The results are shown in Table 2.

[0150] <How to measure step height> Measuring the difference in level between the surface of the base material and the surface of the component (film thickness measurement) Masking Implementation The surfaces of the components were washed with a neutral detergent (Clean Ace), rinsed with ultrapure water, and dried using an air blower. Then, polyimide tape was attached to half of the surface of each component.

[0151] Creating a Boundary The component with the tape attached was placed in a tabletop surface treatment device (UVE-100J, manufactured by Sen Special Light Sources Co., Ltd.), and the surface of the component was irradiated with UV for 20 minutes with the light source of the surface treatment device and the surface of the component within 5 mm of each other. The tape was then removed, and the surface of the component was washed with a neutral detergent (Clean Ace), rinsed with ultrapure water, and dried using an air blower.

[0152] Measurement preparation The component was left to stand at 90° C. for 4 hours in a drying oven to dry out the moisture remaining in the first functional portion that could not be completely removed by air blowing.

[0153] Step measurement The interface between the area where the tape was attached (the area where the functional ultra-thin film was deposited) and the area where the tape was not attached (the substrate) was observed using a laser microscope (SFT4500, manufactured by Olympus). The objective lens used was MPLanApoN100xLEXT (numerical aperture 0.95, measurement area 130 x 130 μm), and the magnification was set to 100 times. At this time, the interface was set so that it was parallel to the Y direction of the stage. After correcting the inclination of the image using the step measurement mode of the analysis software, the linear height profile perpendicular to the boundary line between the first functional part and the substrate in the X direction was calculated, and the step was calculated from the difference in maximum height between the first functional part and the substrate. This operation was performed at five points on the screen, and the average value was taken as the step.

[0154] The film thickness of Example 3 was 87 nm. The sputtering rate of the first functional part calculated from the measured film thickness and the sputter disappearance time (1340 seconds) of the first functional part in the member of Example 3 was 0.065 nm / sec. The film thickness at the upper limit of the sputtering time of the first functional part in the present invention, 1400 seconds, was estimated to be 91 nm, and it was confirmed that the film thickness satisfies the definition of "ultrathin film" in the present invention, which is a film thickness of 100 nm or less.

[0155] Alkaline durability of functional ultra-thin films <Exposure of each component to alkali> Each component was immersed in a 0.2% NaOH aqueous solution (diluted with ion-exchanged water) maintained at 40°C. The immersion time was 60 minutes. Each component was removed from the NaOH aqueous solution and washed, after which the sulfur or nitrogen atomic concentration in the first functional portion, the hydrophilic group remaining rate, the water stain removability, and the water contact angle of the surface of each component were evaluated using the methods described below. The results are shown in Table 2.

[0156] <Measurement of sulfur atom (S) and nitrogen atom (N) concentrations in the first functional part after exposure to alkali> The atomic concentration of the first functional part after exposure to alkali of each member was measured by XPS. A survey spectrum was obtained by XPS measurement under condition 3. From the obtained spectrum, the C1s peak was charge-corrected to 284.8 eV using data analysis software Avantage (Version 5, Thermo Scientific), and the background was removed by the Shirley method for the peak based on the electron orbit of each measured atom, and the peak area intensity was calculated, and an analysis process was performed in which the peak area intensity was divided by a sensitivity coefficient specific to the device previously set in the data analysis software, and the atomic concentration of sulfur or nitrogen was calculated with the total detected atoms as a modulus. Here, Examples 1 to 6 and Comparative Examples 1 to 3 measured the atomic concentration of sulfur contained in sulfonic acid groups, Examples 7 and 9 measured the atomic concentration of nitrogen contained in quaternary ammonium groups, Example 8 measured the atomic concentration of nitrogen contained in amide bonds, and Example 10 measured the atomic concentration of sulfur contained in anionic and amphoteric sulfonic acid groups and the atomic concentration of nitrogen contained in amphoteric quaternary ammonium groups.

[0157] <Calculation of hydrophilic group remaining rate after exposure to alkali> The ratio of the atomic concentration of sulfur or nitrogen in the first functional part of each component after exposure to alkali to the atomic concentration of sulfur or nitrogen in the first functional part of the same component that was not exposed to alkali was calculated, and this was taken as the hydrophilic group residual rate. Note that if the measured value of the latter atomic concentration was greater than the measured value of the former atomic concentration, this difference was due to measurement error in the XPS measurement. In other words, when the calculated value of the hydrophilic group residual rate (%) exceeded 100, this was due to measurement error in the XPS measurement, and the hydrophilic group residual rate was taken as 100%. The results are shown in Table 2.

[0158] <Evaluation of water stain removal ability after exposure to alkali> The anionic (or anionic raw material-containing) samples were evaluated as follows. Contains 9.0-10.0 mg of silica (Si) in 100 mL of water, sodium (Na), Commercially available water containing 1.0-2.0 mg each of calcium (Ca) and magnesium (Mg) and 0-1.0 mg of potassium was diluted 5-fold with ion-exchanged water to prepare test water. 30 μL of this test water was dropped onto the surface of each component that had not been exposed to alkali, and onto the surface of each component that had been exposed to alkali for 0 seconds to 60 minutes, and these components were dried for 1 hour in a constant temperature and humidity chamber set at a temperature of 80°C (without humidity control) under atmospheric pressure, forming water stains on the surface of each component.

[0159] A bathroom sponge (Scotch-Brite (registered trademark) Bath Shine antibacterial sponge (with special abrasive particles), manufactured by 3M Japan) was soaked in ion-exchanged water, and then one push (approximately 1 mL) of bathroom detergent (Bath Magiclean Foaming Spray, manufactured by Kao) was sprayed onto the surface of the sponge to create a foamed detergent.

[0160] The surface of each component on which water stains had formed was applied with a sponge with a load of 800g / cm 2The plate was pressed against the surface of each component with a pressure of 0.01 mm and slid back and forth 10 times. After the slid, it was visually confirmed whether the water scale formed on the surface of each component had been completely removed. If the water scale had been completely removed, it was determined that the alkali resistance of the second functional part was very good and that the hydrophilicity of the first functional part was also good, and this was indicated by a "◎". On the other hand, if even a small amount of water scale remained, the plate was slid back and forth 10 more times. After a total of 20 slids, it was visually confirmed whether the water scale formed on the surface of each component had been completely removed. If the water scale had been completely removed, it was determined that the alkali resistance of the second functional part was good and that the hydrophilicity of the first functional part was also good, and this was indicated by a "○". On the other hand, if water scale still remained, it was determined that the alkali resistance of the second functional part was poor and that the hydrophilicity of the first functional part had been impaired, and this was indicated by a "×".

[0161] <Water contact angle on the surface of a component after exposure to alkali> After exposure to alkali, 2 μL of ion-exchanged water was dropped onto the surface of each component, and the static contact angle of the droplet was measured after 5 seconds. The contact angle was measured using a contact angle meter (model number: DMs-401, manufactured by Kyowa Interface Science Co., Ltd.) and the static contact angle was calculated using the θ / 2 method.

[0162] [Table 2] [Explanation of symbols]

[0163] 10. Materials 1. First Functional Section 2. Second Functional Section 21 Bonding point with the base material 3, reactive silyl group, hydroxyl group contained in the reactive silyl group, hydroxyl group obtained by hydrolysis of a hydrolyzable group, hydrogen atom contained in the hydroxyl group, oxygen atom 22 Repeating units of hydrocarbon groups, alkyl groups, and methylene groups (-CH2-) 23 Binding functional group 3. Substrates containing metal oxides

Claims

1. A substrate comprising a metal oxide; A second functional portion formed on a surface of the base material; a first functional part which is bonded to the second functional part and contains one or more atoms selected from the group consisting of a sulfur atom (S), a phosphorus atom (P), a nitrogen atom (N) and an oxygen atom (O); A member comprising: the outermost surface of the member is the outermost surface of the first functional portion, When the surface of the member is analyzed in the depth direction by X-ray photoelectron spectroscopy (XPS) in combination with argon sputtering, the member satisfies the following requirements (I), (II), and (III): (I) Argon sputtering is started from the surface of the member in accordance with the following condition 1 (0 second), and the first functional portion is deemed to have disappeared because it satisfies the following requirement A (t 1 Sputtering time T 1 (t 1 -0) is 50 seconds or more and 1400 seconds or less; (II) At the time when the first functional portion is deemed to have disappeared because it satisfies the following requirement A, an XPS scan analysis is performed according to the following condition 2, and peak separation is performed in the range from 279.0 eV to 292.0 eV in the C1s measurement range. The ratio of the peak area intensity of the carbon atom attributable to the C-C bond (284.8 eV) to the sum of the peak area intensity of the carbon atom attributable to the C-C bond (284.8 eV), the peak area intensity of the carbon atom attributable to the C-O bond (287.1 eV), and the peak area intensity of the carbon atom attributable to the O=C-O bond (289.2 eV) is 88% or more and 100% or less; (III) The second functional portion is argon sputtered from its surface in accordance with the following condition 1, and the time (t 2 Sputtering time T 2 (t 2 -t 1 ) is 105 seconds or more and 360 seconds or less; Fulfilling The condition 1 is X-ray conditions: monochromatic AlKα radiation, 30 W, 12 kV Analysis area: 200μmφ Neutralization gun conditions: 0.1 V, 200 μA Photoelectron take-off angle: 90° Time Per Step: 10ms Sweep: 2 times Pass energy: 200eV Survey energy range (step size): 0 eV-1350 eV (0.1 eV) Inert gas species: Ar Sputtering voltage: 200 V Sputtering area: 2 mm x 2 mm Sputter cycle: 5 seconds and The requirement A is: After charge correction with the C1s peak set at 284.8 eV, the background is removed by the Shirley method for the peak based on the specified element, the peak area intensity is calculated, and an analysis process is performed in which the peak area intensity is divided by a sensitivity coefficient specific to the device that is preset in the data analysis software, and the atomic concentration of each of sulfur atoms, nitrogen atoms, and phosphorus atoms is 1.0 atm% or less, and the oxygen atomic concentration excluding the oxygen atomic concentration derived from oxides contained in the base material is 6.0 atm% or less, with the total detected atoms as the modulus. and The condition 2 is X-ray conditions: monochromatic AlKα radiation, 30 W, 12 kV Analysis area: 200μmφ Neutralization gun conditions: 0.1 V, 200 μA Photoelectron take-off angle: 90° Time Per Step: 50ms Sweep: 5 times Pass energy: 55eV Analyzed element (energy range, step size): C1s (279.0 eV-292.0 e V, 0.05 eV) Inert gas species: Ar and The requirement B is: After charge correction with the C1s peak set at 284.8 eV, the background is removed by the Shirley method for the peak based on the specified element, the peak area intensity is calculated, and an analysis process is performed in which the peak area intensity is divided by the sensitivity coefficient specific to the device that is preset in the data analysis software, and the carbon atom concentration, with the total atoms detected as the modulus, is 2.5 atm% or less. is A member characterized in that

2. 2. The member according to claim 1, wherein the sputtering time T1 of the first functional portion is from 50 seconds to 1400 seconds, and the sputtering time T2 of the second functional portion is from 130 seconds to 360 seconds.

3. 2. The member according to claim 1, wherein the sputtering time T1 of the first functional portion is from 85 seconds to 1400 seconds, and the sputtering time T2 of the second functional portion is from 130 seconds to 360 seconds.

4. 2. The member according to claim 1, wherein the sputtering time T1 of the first functional portion is 95 seconds or more and 1400 seconds or less, and the sputtering time T2 of the second functional portion is 130 seconds or more and 360 seconds or less.

5. The member according to claim 1 , wherein the substrate comprises a base material and a region containing a metal oxide on a surface side of the substrate.

6. The member according to claim 5 , wherein the region is a layer made of a metal oxide provided on the surface side of the substrate.

7. A method for producing a component according to any one of claims 1 to 6, comprising the steps of: (a) providing a substrate; (b) applying a composition for forming a second functional part to the surface of the substrate to form a second functional part, The composition comprises compound A and compound A', The compound A has an alkyl group, a functional group capable of bonding to a metal oxide on one end of the alkyl group, and a bonding functional group on the other end of the alkyl group, The compound A' has an alkyl group and a functional group capable of bonding to a metal oxide on one end of the alkyl group, and does not have a bonding functional group on the other end of the alkyl group, The alkyl group contained in the compound A and the compound A′ has more than 11 carbon atoms. A process characterized by: (c) applying a composition containing a compound B having a reactive functional group capable of reacting with the binding functional group and a hydrophilic group to the surface of the second functional part to form a first functional part; The method includes at least the following steps.

8. A method for producing a component according to any one of claims 1 to 6, comprising the steps of: (a) providing a substrate; (b') applying a composition for forming a second functional part to the surface of the substrate to form a second functional part, The composition includes a compound A' having an alkyl group, a functional group capable of bonding to a metal oxide on one end of the alkyl group, and a bonding functional group on the other end of the alkyl group, The alkyl group contained in the compound A' has 18 or more carbon atoms. A process characterized by: (c) applying a composition containing a compound B having a reactive functional group capable of reacting with the binding functional group and a hydrophilic group to the surface of the second functional part to form a first functional part; The method includes at least the following steps.

9. 9. The method according to claim 7, wherein the functional group capable of bonding with the metal oxide is a hydrolyzable silyl group, and the bonding functional group is a 2-bromo-2-methylpropanoic acid group.

Citation Information

Patent Citations

  • Hydrophilic treatment coating composition and hydrophilic treatment method

    JP2016020461A

  • High-sensitivity electrochemical biosensor

    JP2022088296A

Cited By

  • Solid-state imaging device

    CN122825548A